73 β1-ADRENERGIC RECEPTOR GENE MODULATES THE EFFECT OF HEART RATE ON ARTERIAL STIFFNESS: THE BOGALUSA HEART STUDY. Issue 1 (1st January 2007) - Chen, W.; Srinivasan, S. R.; Boerwinkle, E.; Berenson, G. S.
Abstract : Introduction: Heart rate and sympathetic nervous activity are important determinants of arterial stiffness. However, whether the relationship between heart rate and arterial stiffness is modulated by β1 -adrenergic receptor (β1 -AR) gene variation is not known. This study examines the genetic modulation by β1 -AR gene polymorphism (Arg389Gly) on the effect of heart rate on arterial stiffness in young adults. Methods: The study cohort included 183 blacks and 502 whites aged 19 to 44 years enrolled in the Bogalusa Heart Study. Aortofemoral pulse wave velocity (af-PWV) was measured by echo-Doppler. Results: Heart rate was significantly associated with af-PWV in blacks, whites, and the total sample. However, there was no difference in heart rate between carriers and noncarriers of Gly389 allele in both blacks and whites. Carriers versus noncarriers of the Gly389 allele showed higher values of af-PWV (5.29 m/sec vs 5.19 m/sec, p < .01) in whites but not in blacks (5.40 m/sec vs 5.37 m/sec, p = .524). In multivariate regression analysis for the total sample, both heart rate and Gly389 allele were significantly and positively associated with af-PWV, adjusting for race, sex, age, body mass index, and pulse pressure. Furthermore, the adverse positive relationship between heart rate and af-PWV was noted only among carriers of Gly389 allele (comparison of slopes p = .018). Conclusions: β1 -AR gene modulates arterial stiffness and its association with heart rate in young adults.